STRATEGI DISEMINASI INOVASI PERTANIAN DALAM MENDUKUNG PEMBANGUNAN PERTANIAN (Forum Penelitian Agro Ekonomi, 2024)
Dissemination of innovation of research results/agricultural assessment is an important communication activity in the process. Problems of dissemination agricultural innovation with technology adoption department, aerial result and socio-economic development of farmers. The gap between ideal conditions and the conditions under construction is an interesting thing to look at. This paper is for the process and implementation of dissemination of agricultural innovation, strategy dissemination of agricultural innovation. This paper is a review of some relevant literature and research results. The strategy of dissemination of agricultural innovation can be divided into two, while at the central and regional levels with the understanding of user innovation and the needs or preferences of users of agricultural innovation. Sources of agricultural innovation at the central level derived from IAARD and as a user are BPPSDMP, technical directorate general, business actors (industry / business / private), and main actors (farmers). The dissemination channels that can be done are dominated through electronic media with extensive coverage and print media (books and journals), as well as some interpersonal media (meeting and meeting forums). The support of facilities and facilities becomes a decisive tool for the user's ability to access agricultural innovation. The source of agricultural innovation at the regional level is BPTP with village extensionists as intermediate users and farmers as end users. The role of extensionists and community leaders as motivators is still dominant at the farm level. Thus dissemination channels can be done through interpersonal media such as demonstration plots, technology titles, field meetings, or group meetings. At the level of the Region that is urgently needed.